Surgical management of postintubation tracheal stenosis: a clinical case - Boyko Yavorov; Vladimir Aleksiev; Hristo Stoev; Martin Karlyukov; Filip Shterev; Stanislav Kartev; Zaprin Vazhev (Folia Medica, 2026)
Abstract Postintubation tracheal stenosis, a complication of prolonged mechanical ventilation via orotracheal intubation, often presents with stridor and dyspnea due to tracheal fibrosis and scarring, typically distal to the cricoid cartilage. Its complex nature necessitates a multidisciplinary approach and expertise in tracheal, thyroid, mediastinal, and neurovascular surgical techniques. This case report details the clinical management of postintubation tracheal stenosis, highlighting a successful tracheal resection and anastomosis procedure. A patient, S.A., presented at the Thoracic Surgery Department, UMHAT Kaspela, Plovdiv, with respiratory distress, including stridor and dyspnea, following 10 days of mechanical ventilation for aspiration pneumonia. The diagnostic workup included thoracic computed tomography (CT), video bronchoscopy, echocardiography, and pulmonary function tests. Surgical intervention involved Kocher’s cervicotomy, tracheal mobilization, circular resection of the stenotic segment, and termino-terminal anastomosis. Intraoperative video bronchoscopy confirmed stenosis location and post-anastomosis tracheal integrity. The patient recovered uneventfully and was discharged in satisfactory condition. Surgical management of postintubation tracheal stenosis, when guided by early diagnosis, precise imaging, and a multidisciplinary approach, yields favorable outcomes. This case underscores the importance of surgical expertise and meticulous planning in achieving successful results.